Topic of the Imaginative Text and Its Philosophical and Linguistic Presentation - Blokh, Mark Yakovlevich; Asratyan, Zoya Dmitrievna; Asratyan, Norair Martinovich (Journal of History Culture and Art Research, 2019)
This paper discusses various approaches to the nature of the imaginative literary text, especially in the 20th century. Considering the topic as a semantic focus, as an integrating phenomenon compositionally uniting all the elements of a text, the authors proceed from the idea that the methodological basis of this principle of research is represented by the theory of dicteme which is understood as a minimal unit of thematization (topicalization), styling and conceptualizing the text. The real or unreal world reflected in imaginative literature is given to the reader through the individual author’s perception which is conceptualized. This conceptualization is observed at the level of dicteme, manifested, on the one hand, in the ideological validity of the topic, and on the other hand, in the thematic (topical) role of the concept. The topic of a work of art is the semantic core itself that concentrates the main idea, the key problem essential for the author, his/her intention and purpose, and, together with this, the topic as such organizes the relevant text structure that connects the parts around that core. This topical construct is built by dictemes that form the composition of a text. At the same time, the authors caution against one-sided approaches, both elementary and holistic, in identifying the topic. To identify the topic, both by formal definition and adequate description it is proposed to use a judgment with its categorial-propositional structure, including subject/s, objects, predicates, attributes, certain adverbial characterisistics, etc.